The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0049467
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Mutagen Dosage to Induce Point-Mutations in Synechocystis sp. PCC6803 and Its Application to Promote Temperature Tolerance

Abstract: Random mutagenesis is a useful tool to genetically modify organisms for various purposes, such as adaptation to cultivation conditions, the induction of tolerances, or increased yield of valuable substances. This is especially attractive for systems where it is not obvious which genes require modifications. Random mutagenesis has been extensively used to modify crop plants, but even with the renewed interest in microalgae and cyanobacteria for biofuel applications, there is relatively limited current research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
1
42
1
Order By: Relevance
“…We selected random chemical mutagenesis with ethyl methanesulfonate (EMS), as it is an alkylating agent known to cause mainly transition mutations (27,28). EMS and other mutagens are used routinely in industrial settings to enhance the qualities of industrial microbial strains (28)(29)(30)). An enrichment method was established in which an excess of immobilized anti-SpaC IgG was used to trap piliated L. rhamnosus GG cells while nonpiliated mutants remain unbound.…”
Section: Resultsmentioning
confidence: 99%
“…We selected random chemical mutagenesis with ethyl methanesulfonate (EMS), as it is an alkylating agent known to cause mainly transition mutations (27,28). EMS and other mutagens are used routinely in industrial settings to enhance the qualities of industrial microbial strains (28)(29)(30)). An enrichment method was established in which an excess of immobilized anti-SpaC IgG was used to trap piliated L. rhamnosus GG cells while nonpiliated mutants remain unbound.…”
Section: Resultsmentioning
confidence: 99%
“…Tillich et al (2012) showed that the UV-C dosage giving a survival rate of ca. The survival rates of cells were 100.0 AE 5.6% (for no irradiation), 20.8 AE 4.7% (for 15 min irradiation), 5.7 AE 1.6% (30 min), 4.4 AE 0.3% (45 min), 0.7 AE 0.1% (60 min), and 0.0 AE 0.0% (90 min).…”
Section: Resultsmentioning
confidence: 99%
“…The exposure time for mutagenesis was adjusted so that the survival rate was about 10% (Tillich et al, 2012). The plate was irradiated with UV-C using a sterilization lamp (lmax ¼ 253.7 nm, GL-15, Hitachi Appliances, Inc.,) at a distance of 70 cm.…”
Section: Condition Of the Mutagenesis By Uv-c Exposurementioning
confidence: 99%
“…Increases of stress tolerance against, for example, temperature (Tillich et al, 2012) or salinity (Bagchi et al, 2007;Ruffing, 2011) not only leads to enhanced longevity, but may also serve to protect cyanobacterial cultures against contamination with other (heterotrophic) microorganisms, as happens for, for example, Arthrospira mass cultivation.…”
Section: Requirements Of Industrial Production Strainsmentioning
confidence: 99%